"Us Refugees, the Flotsam and Jetsam of Death”: the Monsters of Being Human as Ethnic Outsiders, Migrants and Asylum Seekers (Altre Modernità, 2020)
Being Human was a British television series broadcast by BBC Three between 2008 and 2013. Its main characters are a ghost, a vampire and a werewolf, who live together and try to lead a normal life among humans; however, their integration into society is a constant struggle.Since Being Human is centred on inclusion, exclusion and belonging, the story evokes real-life situations of marginalisation; following Lampert-Weissig’s suggestion about the relevance of the characters’ ethnicity (an Irish, a Jewish and a mixed-race person), which makes them “double outsiders” (65), my essay proposes an analysis of the three main characters in seasons 1-3 of Being Human as tropes for ethnic outsiders, migrants and asylum seekers in the UK.I will first consider each character individually, because each one of the three tropes (werewolf, vampire, ghost) has its own history and evolution in folklore, literature and cinema and, therefore, each one of the three protagonists is particularly suited for introducing different perspectives on foreignness and marginalisation. I will then discuss how Being Human addresses the issue of social exclusion and how the show’s final message, while progressive at first sight, is actually problematic and ambiguous.
Keywords: vampire; werewolf; ghost; migrants; outsiders; marginalisation